P.033 Eptinezumab reduced acute medication use in patients with chronic migraine and medication-overuse headache: subgroup analysis of Promise-2. (November 2021) - Marmura, MJ; Diener, H; Hirman, J; Cady, R; Brevig, T; Brunner, E; Minhas, S; Mehta, L
Abstract : Background: Eptinezumab is a preventive migraine treatment approved in the US. We evaluated the impact of eptinezumab on acute headache medication (AHM) use in patients diagnosed with chronic migraine (CM) and medication-overuse headache (MOH) in PROMISE-2. Methods: PROMISE-2 randomized patients with CM to eptinezumab 100mg, 300mg, or placebo for 2 intravenous doses administered every 12 weeks. Trained investigators diagnosed MOH at screening using 3-month medication history and ICHD-3b criteria. Endpoints included days/month of any AHM use (days of ≥1 medication class), total AHM use (summed days for each medication class), and triptan use over Weeks 1-12 and 13-24. AHM classes included triptan, ergot, opioid, simple analgesic, and combination analgesic. Results: Of 1072 PROMISE-2 patients, 431 (40.2%) were diagnosed with MOH (100mg, n=139; 300mg, n=147; placebo, n=145). During the 28-day baseline period, mean days of any AHM was 16.4, total AHM was 20.4, and triptan was 8.9 across treatment arms. Over Weeks 1-12, mean days/month of any AHM was 8.8 (100mg), 9.9 (300mg), and 11.8 (placebo); total AHM was 10.8, 12.2, and 14.8; triptan was 4.3, 4.4, and 6.4. Similar or lower rates were observed over Weeks 13-24. Conclusions: In patients diagnosed with both CM and MOH, eptinezumab treatment reduced AHM use.